Antibiotic resistance pattern and molecular detection of ESBL-associated genes in E. coli from surface and wastewater of Islamabad capital territory, Pakistan - Aitezaz Ahsan; Tariq Atta Ur Rehman; Hamid Irshad; Muhammad Armaghan Shahzad; Abubakar Siddique; Asma Jamil; Adnan Ali (IWA Publishing, 2022)
The goal of this study was to determine how surface and wastewater contribute to the contamination of the environment with an extended-spectrum β-lactamase-producing Escherichia coli (ESBL E. coli). Water samples (n = 32) were collected from eight different locations of Islamabad and processed for microbiological and molecular analyses of E. coli and ESBL E. coli. Antimicrobial susceptibility testing was carried out to determine the resistance pattern of the isolates. A total of 21 water samples were contaminated with E. coli and 15 isolates were identified as ESBL producers harboring blaTEM (40%) and blaCTX-M (33.33%) genes. Interestingly, all the ESBL E. coli isolates showed the least resistance against second-generation Cephalosporins compared to other generations. Moreover, the study showed that the aquatic environment is harboring multidrug-resistant E. coli; therefore, it may act as a source of transmission to humans. The recovery of ESBL E. coli isolates resistant to higher generation Cephalosporins, Monobactam, and Carbapenems from water samples indicated an alarming situation. Thus, there is an urgent need to treat water efficiently for microbial decontamination to minimize the transmission of antimicrobial-resistant (AMR) bacteria. HIGHLIGHTS This is the first study of its type from Pakistan which describes the occurrence of AMR bacteria in a water body starting from upstream to its subsequent downstreams.; All (100%) of the ESBL E. coli isolates had multidrug resistance.; The most commonly detected ESBL-encoding gene in ESBL E. coli isolates was blaTEM.; ESBL E. coli isolates resistant to last-resort antibiotics were recovered during the study.;